Efektivitas Sistem Bagi Hasil pada Perbankan Syariah versus Sistem Bunga pada Perbankan Konvensional - Hidayat Hidayat (Universitas Islam Raden Rahmat, 2025)
This study aims to analyse the effectiveness of profit-sharing systems in Islamic banking compared to interest-based systems in conventional banking, particularly in terms of profitability, risk management, and economic fairness. The main focus is on mudharabah and musyarakah contracts as the main instruments of profit-sharing systems, as well as fixed and floating interest rates in conventional banks. The research method used is qualitative with a descriptive-comparative library research approach. Data was collected through document reviews, financial reports, and scientific literature from official institutions such as the OJK, BI, and academic publications. The results show that the interest system is proven to be superior in generating short-term profitability and margin stability. However, the profit-sharing system provides a more equitable and participatory approach through risk-sharing mechanisms and transparency, despite facing challenges of moral hazard and low sharia literacy. The recommendations of this study emphasise the importance of improving the quality of risk management, transparency, the use of information technology, and sharia financial literacy to optimise the effectiveness of the profit-sharing system as an equitable alternative to the conventional interest system.